الغيرة الزوجية: أسبابها وآثارها وعلاجها في ضوء السنة النبوية ................................................................. Causes of Ardency between Co-Wives and Its Treatment in the Light of Prophetic traditions - بني عامر أسماء محمد أمين حسن (الدراسات الإسلامية, 2019)
This research paper shows the basic causes of ardency between co-wives in the case of polygamy and presents the spiritual medication of this sickness in the light of Prophetic traditions. I have focused on traditions related to the topic and analytically studied them. Ardency between co-wives is a social and legal issue. Present legal systems banned polygamy due to its unpleasant effects on society. However, this is not a proper solution to this problem. It is a natural phenomenon that when a person marries more than one woman, they usually face the problem of jealousy, which not only badly effects the relations of the spouses and their kids, but also creates social and moral disorder in society. Islamic teachings do not deny the existence of ardency between co-wives but they provide proper spiritual medication in this regard. In the Prophetic traditions one finds enough material which deals with the said issue from psychological, ethical, and spiritual points of view. This research work highlights theses aspects to some extent. Both deductive and inductive methods of research have been adopted in this paper. I have addressed in this paper following questions: What is ardency? How many types of ardency are there? What are the basic root causes of ardency? Why is ardency not found in some cases of polygamy? What is the Islamic approach to this problem? Keywords: ardency, co-wives, Prophetic traditions, polygamy.